Paraffin Wax [As a Phase Changing Material (PCM)] Based Composites Containing Multi-Walled Carbon Nanotubes for Thermal Energy Storage (TES) Development - Norah Hamad Almousa; Maha R. Alotaibi; Mohammad Alsohybani; Dominik Radziszewski; Saeed M. AlNoman; Bandar M. Alotaibi; Maha M. Khayyat (Crystals, 2021)
Thermal energy storage (TES) technologies are considered as enabling and supporting technologies for more sustainable and reliable energy generation methods such as solar thermal and concentrated solar power. A thorough investigation of the TES system using paraffin wax (PW) as a phase changing material (PCM) should be considered. One of the possible approaches for improving the overall performance of the TES system is to enhance the thermal properties of the energy storage materials of PW. The current study investigated some of the properties of PW doped with nano-additives, namely, multi-walled carbon nanotubes (MWCNs), forming a nanocomposite PCM. The paraffin/MWCNT composite PCMs were tailor-made for enhanced and efficient TES applications. The thermal storage efficiency of the current TES bed system was approximately 71%, which is significant. Scanning electron spectroscopy (SEM) with energy dispersive X-ray (EDX) characterization showed the physical incorporation of MWCNTs with PW, which was achieved by strong interfaces without microcracks. In addition, the FTIR (Fourier transform infrared) and TGA (thermogravimetric analysis) experimental results of this composite PCM showed good chemical compatibility and thermal stability. This was elucidated based on the observed similar thermal mass loss profiles as well as the identical chemical bond peaks for all of the tested samples (PW, CNT, and PW/CNT composites).